Job Satisfaction and Workplace Harassment: An Investigation in the Nepalese Development Banking Sector - Neupane, Nisha (Devkota Journal of Interdisciplinary Studies, 2023)
In today’s context, workplace harassment has become a widespread issue, and its repercussions extend to an employee’s personal life, family, and career. The principal objective of this research endeavor was to examine the occurrence of workplace harassment and the resultant consequences for job satisfaction in the banking sector of Nepal. The findings unequivocally demonstrate that various forms of harassment including verbal, physical, and psychological have a substantial and statistically significant effect on the job satisfaction of employees. Furthermore, this study establishes that these forms of harassment-verbal, physical, and mental – are positively and significantly correlated with one another. Sadly, it is evident that these types of harassment disproportionately affect assistant and junior-level officers, leading to a notable reduction in job satisfaction within their workplace.